Evaluation of Solar Drying on Drying Behaviour and Drying Kinetics of Penaeus vannamei. Issue 4 (21st April 2022) - Wang, Suwen; Jin, Jingyu; Suo, Ran; Wang, Yajiao; Wang, Jie; Wang, Wenxiu; Liu, Yaqiong; Chitrakar, Bimal
ABSTRACT: This work aimed to evaluate the effects of solar drying (SD) on physico-chemical properties, drying kinetics, and energy consumption to dry Penaeus vannamei, considering natural drying (ND) and hot-air drying (HD) as references. Compared with ND and HD, SD exhibited the shortest time when the moisture content (MC) was reduced from 73% to 18%, and the effective moisture diffusivity was in the range of 151.26 × 10-10 to 9.26 × 10-10 m2s-1. The two-term model was the most suitable for fitting of the drying curves by analyzing six theoretical models. Additionally, the superior texture, brighter color, and higher sensory scores were obtained by SD. SD application brought about changes in shrinkage and rehydration. And the different drying methods presented significant effects on energy consumption; of which, SD saved the most energy (3.00 kWh). Impact analysis showed that SD is a suitable solution for preserving Penaeus vannamei with environmental sustainability. Abstract : uf0001